Implementation of Stunting Management Policy in Bandung Regency in 2024 - Setiawan, Andika Doni (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Study purpose. This study aims to analyse the implementation of stunting prevention policies in Bandung Regency. This policy is regulated through Regent Regulation No. 74 of 2019 concerning the Acceleration of Stunting Prevention and Control. The theory used is Van Meter and Van Horn's policy implementation theory, which includes variables such as policy standards and objectives, resources, inter-organisational communication, characteristics of implementing organisations, and economic, social, and political factors. Materials and methods. This study used a qualitative descriptive method with data collection techniques through in-depth interviews, observations, and document studies. Results. The results showed that Bandung Regency had made various cross-sectoral convergence efforts to reduce the prevalence of stunting. The main supporting factors included the high commitment of the local government, the availability of integrated health service posts (posyandu), and budget support through the regional budget (APBD). However, the study also identified a number of inhibiting factors, such as limited human resources and capacity, low public awareness, weak cross-sectoral coordination, and challenges in budget allocation that is not yet fully focused on tackling stunting. Conclusion. The conclusion of this study is that the implementation of the Stunting Management Policy in Bandung Regency in 2024 has been quite successful, but improvements are still needed in terms of cross-sectoral synergy, increasing human resource capacity, and strengthening public education. As a means to this end, the local government needs to optimise the role of integrated health service posts (posyandu), improve cross-sector coordination, utilise technology for data monitoring, and engage the private sector and the community to support efforts to accelerate stunting reduction.